KEGIATAN EKTRAKURIKULER KARAWITAN UNTUK MENUMBUHKAN CINTA BUDAYA JAWA PADA SISWA DI SDN KEBONSARI I TUBAN - Ainiatun Nafiah; Wendri Wiratsiwi (ELENOR: Elementary School Journal, 2024)
The extracurricular programmes run by schools have the potential as a means of character education. One of them is an extracurricular karawitan. The purpose of this study is to describe the extracurricular application of karawitan that exists in the Kebonsari 1 Tuban SDN. The method used in this research is a descriptive method. The results of this study describe that the extracurricular karavitan activities in the State SD Kebonsari I Tuban are carried out every Monday afternoon at 15.30-17.00 with the accompaniment of a trainer and supervisor. Currently it involves only about 34-35 students, with about 20 students actively participating. The extracurricular trainer of the Karawitan at the State SD Kebonsari I Tuban applied simple teaching methods. The approach involves writing notes of songs to be played and individual training for each gamelan instrument beat. The SD has 33 fairly complete gamelan musical instruments, consisting of 11 types. The extracurricular activities of karawitan bring positive results, seen from students who become accustomed to listening to music with gamelan elements and show interest in the kind of music. It's proved by their music choices during art lessons, there's even a demand to use modified music with gamelan elements during morning gymnastics. Keywords: Karawitan, love of culture